Numerical Analysis of Thermal Dependence of the Spectral Response of Polymer Optical Fiber Bragg Gratings - Hisham, Hisham K. (Iraqi Journal for Electrical and Electronic Engineering, 2016)
The thermal dependence of the spectral response (i.e. transmission, reflection and time delay ( τ r ) responses) of uniform polymer optical fiber (POF) Bragg gratings has been investigated. In addition to the temperature dependence, the effects of grating strength (kL g ) and fiber index modulation ( ∆ n) have been investigated. Besides high capability of tunable wavelength due to the unique large and negative thermo-optic coefficient of POF, the spectral response for POF Bragg gratings show high stability and larger spectrum bandwidth with temperature variation compare with the silica optical fiber (SOF) Bragg gratings, especially with the increase of the kL g value. It was found that by increasing kL g , the peak reflectance value increases and the bandwidth of the Bragg reflector become narrower. Also it’s shown by increasing the kL g value, τ r deceasing significantly and reach its minimum value at the designed wavelength ( λ B ). Furthermore, the τ r for POF Bragg gratings is less than that for SOF Bragg gratings at the same value of kL g . Also it’s found that the peak reflectivity value increases to around 60% when the ∆ n value increases from 1 ˣ 10 -4 to 5 ˣ 10 -4 .